A tailored approach to reduce dose of anti-TNF drugs may be equally effective, but substantially less costly than standard dosing in patients with ankylosing spondylitis over 1 year: a propensity score-matched cohort study - Závada, Jakub; Uher, Michal; Sisol, Katarína; Forejtová, Šárka; Jarošová, Kateřina; Mann, Heřman; Vencovský, Jiří; Pavelka, Karel (Annals of the rheumatic diseases, 2016)
OBJECTIVE: To compare the effectiveness, safety and costs of standard versus individually tailored reduced doses of anti-tumour necrosis factor (TNF) drugs in patients with ankylosing spondylitis (AS) after achieving low-disease activity. METHODS: This was a single-centre prospective observational study performed within the ATTRA registry. The anti-TNF dose tapering strategy was chosen by treating physicians, without prespecified protocol. We used propensity score (PS) methodology to identify two cohorts of patients matched for relevant baseline characteristics who were treated with either reduced (n=53) or standard (n=83) doses of TNF inhibitors. One-year outcomes and costs of anti-TNF drugs were compared between both PS-matched cohorts. RESULTS: In the reduced dosing group, the median dose of TNF inhibitor corresponded to 0.67 and 0.5 of the standard dose initially and at 12 months respectively, and 21% of patients required return to standard dosing regimen. The mean change per year in Bath Ankylosing Spondylitis Activity Index, C-reactive protein , Health Assessment Questionnaire Disability Index and Bath AS functional index, as well as quality-adjusted life-year area under the curve were no different between both groups. The HR (95% CI) of reduced versus standard dosing group for relapse and any adverse event was 1.46 (0.66 to 3.19) and 0.56 (0.22 to 1.44), respectively. Mean difference (95% CI) in cost of anti-TNF drugs was €-4214 (-4707 to -3701) per year of treatment in favour of reduced dosing strategy. CONCLUSIONS: In patients with AS after reaching low-disease activity, a tailored approach to reduce doses of anti-TNF drugs produced similar clinical outcomes at 1 year, but was substantially less costly.
Keywords: recidiva; náklady na léky; Disability Evaluation; Infliximab; ankylózující spondylitida; Humans; Etanercept; lidé středního věku; C-reaktivní protein; posuzování pracovní neschopnosti; Drug Costs; antirevmatika; infliximab; Female; Area Under Curve; dospělí; udržovací chemoterapie; tendenční skóre; etanercept; Time Factors; lidé; adalimumab; Anti-TNF; přežití bez známek nemoci; časové faktory; Maintenance Chemotherapy; Adalimumab; TNF-alfa; Quality-Adjusted Life Years; Adult; Follow-Up Studies; ženské pohlaví; stupeň závažnosti nemoci; Male; Middle Aged; Spondylitis, Ankylosing; Czech Republic; Ankylosing Spondylitis; Severity of Illness Index; Recurrence; kvalitativně upravené roky života; plocha pod křivkou; Disease-Free Survival; Tumor Necrosis Factor-alpha; Česká republika; mužské pohlaví; prospektivní studie; C-Reactive Protein; Antirheumatic Agents; následné studie; Treatment; Propensity Score; Prospective Studies